Effective dispute resolution in Takaful-related cases: A case study of the financial mediation bureau in Malaysia - Oseni, Umar Aimhanosi (2013)
Until recently, discussions of issues relating to dispute resolution in the Islamic finance industry have remained well in the background, as the stakeholders in the industry strived to promote this hitherto niche industry for a global recognition. Interest in studies relating to dispute resolution in Islamic banking and finance has mushroomed over the past few years, while the takaful component of the industry has been neglected even though insurance-related issues are more amenable to disputes than others particularly when there are differences regarding claims, limitation of usage of insured property, variations in insurance agreement, and disputes between the Sharī‘ah Supervisory Board and the takaful operator. As a result, the DOME International Takaful Report 2012-2013 briefly examines the relevance of arbitration and dispute resolution in takaful and Retakaful cases. Against this backdrop, this paper examines the need for effective dispute resolution in takaful-related cases with special reference to the model of the Financial Mediation Bureau (FMB) in Malaysia. With an in-depth analysis of the 2011 and 2012 takaful-related cases mediated by FMB, this paper finds that parties do prefer fast and cost-efficient processes for dispute resolution, as takaful schemes also require efficient dispute resolution processes like other commercial transactions. Such successes recorded in Malaysia could be replicated in other jurisdictions offering Islamic financial services. This is important in the drive towards enhancing the legal and regulatory landscape for Islamic financial markets.